Investigations on Andaman and Nicobar Islands Woods for Different Grades of Paper - Singh, Man Mohan; Madan, R. N.; Dhawan, Rita; Karira, K. K.; Karira, B. G. (Indian Forester, 1981)
Laboratory scale experiments were carried out on the production of wrapping, writing, printing and newsprint grade pulps from seven species by different pulping processes like sulphate, neutral sulphite, semi-chemical (N.S.S.C) and cold soda Unbleached pulps suitable for wrapping papers were obtained in satisfactory yield, and having satisfactory strength properties by using sulphate and (N.S.S.C.) process. For writing printing,paper the pulps were bleached by CEH sequence. Bleached pulps in satisfactory yield and good strength properties were obtained. Pulps in high yield could be obtained by cold soda process. Which when admixed with 28 bamboo sulphate pulp were considered to be suitable for newprint. Comparative suitability indice of wood, for wrapping and writing printing papers were calculated. From the results it Can be conciuded that all the seven species are suitable for wrapping, writing, printing and newsprint grade pulps.